Determination of wear pattern of cutting elements of tillage machines - Пасюта, Андрей Григорьевич (Technology audit and production reserves, 2014)
The problems of theoretical researches of wear surface of the working tools’ cutting elements of tilling machines are shown in the article. The main aim of the research is to develop a process of hardening, providing increase their longevity and quality of soil treatment. The interaction process of working tools of tilling machines with soil abrasive environment during their movement is characterized by the interaction of abrasive soil on wedge with a flat working surface. This article describes how to influence the impact of soil on a wedge from material deformation nature, the wedge parameters, physical and mechanical properties and soil conditions. The theoretical dependence of these parameters allows to provide the wear of the cutting elements of tilling machines, which will contribute to reduction of the dynamics of their wear. To ensure the longevity of cultivator tooth is necessary reducing the size of their wear is necessary to reduce the ability of abrasive wear out and will provide options of cultivator tooth, which will reduce the dynamics of wear. The research results will select and apply an effective technology of hardening of cutting elements of tilling machines during wear and recovery.